2015
DOI: 10.1039/c5ra17316g
|View full text |Cite
|
Sign up to set email alerts
|

The influence of aluminum chloride on biosynthetic schwertmannite and Cu(ii)/Cr(vi) adsorption

Abstract: In this study, aluminium chloride modified schwertmannite was biosynthesized using Acidithiobacillus ferrooxidans. Heavy metals can be efficiently removed by the modified biosynthetic schwertmannite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 39 publications
(39 reference statements)
1
10
0
Order By: Relevance
“…When exterior surface reached saturation, palladium ions entered the biomass on the second stage with increased diffusion resistance, resulting in a decrease of diffusion rates (k i2 ). As Min 22,23 reported, the adsorption was controlled by two steps or more, including boundary layer or external diffusion, pore diffusion, surface diffusion and adsorption onto the pore surface, or a combination of several steps, of which the intraparticle diffusion step was the most rate-limiting procedure. The multi-linearity in the shape of the intraparticle diffusion plot had also been observed by Ofomaja in the biosorption of lead, methylene blue and methyl violet onto mansonia wood sawdust.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When exterior surface reached saturation, palladium ions entered the biomass on the second stage with increased diffusion resistance, resulting in a decrease of diffusion rates (k i2 ). As Min 22,23 reported, the adsorption was controlled by two steps or more, including boundary layer or external diffusion, pore diffusion, surface diffusion and adsorption onto the pore surface, or a combination of several steps, of which the intraparticle diffusion step was the most rate-limiting procedure. The multi-linearity in the shape of the intraparticle diffusion plot had also been observed by Ofomaja in the biosorption of lead, methylene blue and methyl violet onto mansonia wood sawdust.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the isotherms with n values greater than unity were classied as L-type isotherms which showed that there was high affinity between adsorbate and adsorbent surface. 23,26 The maximum biosorption capacity calculated from Langmuir isotherm presented in Table 2 was 196.806 mg g À1 for the biosorption of Pd(II). This biosorption capacity is higher than those reported for Racomitrium lanuginosum 27 and Escherichia coli.…”
Section: Resultsmentioning
confidence: 99%
“…It is one of the most effective adsorption materials for heavy metal removal [24,27,28]. Furthermore, after modification by inorganic substances, such as AlPO 4 and AlCl 3 , Schwertmannite shows higher adsorption kinetic, capacities and better selectivity [29,30].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…ln q e = ln K F + 1 n ln C e (11) where C e is the equilibrium concentration of Cu 2+ and q e is the adsorption capacity at equilibrium. K F and n are Freundlich constants.…”
Section: Adsorption Isotherm and Thermodynamic Analysismentioning
confidence: 99%
“…An appropriate amount of copper element is essential to human bodies, but excess copper will result in nausea, vomiting, haemolytic anaemia, neurological abnormalities and even organ failure . In order to remove heavy metal contaminants and eliminate the threat, pioneers explored many feasible methods, including ion exchange, coagulation, biological treatment, chemical precipitation, flotation, membrane osmosis and adsorption . Among these methods, adsorption is frequently used due to its low cost, high capacity, easy handling, good selectivity and non‐pollution …”
Section: Introductionmentioning
confidence: 99%